Examination of the reading comprehension skills of good and poor readers in the dimension of reading components developed by a reading skills assessment tool - Alatlı, Reşat; Güldenoğlu, İsa Birkan; Kargın, Tevhide; Gengeç,Hilal (Turkish Education Association, 2022)
The aim of this study is to develop a Reading Skills Assessment Tool (RSAT) for 2nd, 4th, 6th and 8th grade readers and to assess if there is a significant difference between the decoding and fluent reading skills of good and poor comprehenders. First, validity and reliability studies of the RSAT, which includes the dimensions of decoding, fluent reading, and reading comprehension, were conducted in this direction. The RSAT was finalized with the data collected from 840 participants in validity and reliability studies. Following this, the reading comprehension scores of 150 participants at each grade level were divided into lower and upper 27% groups, and groups with good and poor comprehenders were determined. Then, the differences in the decoding and reading fluency results of the good and poor comprehenders were studied. The results revealed that the decoding and fluency reading performances of good comprehenders were considerably superior to those of the group with poor comprehenders, and the results were reviewed in light of the relevant literature. Consequently, good comprehenders performed better than poor comprehenders in decoding (syllable reading pace, real word reading pace and pseudoword reading accuracy) and fluent reading (correct number of words read per minute). With the research, a formal tool for evaluating reading skills has been added to the Turkish literature, and it has contributed to the elimination of an important limitation in this field. RSAT can be used effectively by experts in scientific studies and by teachers in the evaluation of student performance in practice. In addition, it was emphasized that good and poor readers perform differently in all aspects of reading, and that it is crucial to prevent future problems by conducting the necessary evaluations and interventions at the outset of reading instruction. © 2022 Turkish Education Association. All rights reserved.
Keywords: assessment of reading; components of reading; development of reading; good and poor readers; reading performances of good and poor readers